Deviations from Politeness Principles in Humor Content on The YouTube Account @Tretan Universe - Ramadhani, Fatimah Nurul; Markhamah, M (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe and analyze the forms of politeness principle deviations in humorous content on the @Tretan Universe YouTube account. The phenomenon warrants investigation as it involves intricate communication strategies that balance humor creation with linguistic propriety. Employing a qualitative descriptive approach, this research analyzes utterances from the 22-minute podcast